Clinical Profile of Children Hospitalized with COVID-19 in Indonesia’s District Hospital : A First Year Pandemic Wave Single Centre Study - Luthfiyah, Dina; Shodikin, Muhammad Ali (Smart Medical Journal, 2022)
Background: Children are known to be less infected by Coronavirus disease 2019 (COVID-19) rather than adults. However, children are still a vulnerable group and the incidence of patients admitted to hospital continues to increase. As Indonesia’s district has limited resources during pandemic wave, the data on pandemic cases was still underreported especially cases of children.Methods: This retrospective observational study collected data on pediatric case aged 0 – 18 years old, who were hospitalized at dr. Soebandi Hospital, Jember, Indonesia and confirmed to have COVID-19, from March 2020 to the end of March 2021.Results: 40 children were hospitalized and confirmed COVID-19 during the study period, the majority aged 15 – 18 years (40%), male (65%), and had a history of contact (67.5%). The most common symptoms were cough (85%), fever (67.5%), and shortness of breath (40%). Laboratory results showed that the majority had decreased neutrophils and increased lymphocytes, while most of the patient had normal chest X-rays (52.5%). From 5 pediatric patients who had multimorbidity, 4 patients died. All four had common underweight clinical morbidity, while acute respiratory distress syndrome was dominated the cause of death. The mortality rate in this study reached 10%.Conclusion: The majority of pediatric patients were found to have mild to moderate symptoms with good outcomes. Case mortality rate in this study was lower than national data. Meanwhile, the underweight comorbid in children with COVID-19 was worsening the outcome in this study.